Social changes after the war, 1944 (1944)
1944 1939-1945 "Social changes after the war, 1944" [HFR0147], 1944 This chart comes from 'The Journey Home', a wartime Mass Observation survey for the Advertising Service Guild in 1944. It indicates people's changing aspirations and expectations for life after the war - covering issues such as town planning, unemployment, educational reform, class distinction, nationalisation, social services and Socialism.